Weak and periodical solutions of the navier-stokes equation in noncylindrical domains - Quiroga Gonzáles, Cruz Sonia; Limaco, Juan; Gamboa, Pedro; Barreto, Rioco K. (Pro Mathematica, 2001)
We consider the Navier Stokes equation in noncylindrical domain and prove the existence of weak and periodical solutions.